2020
DOI: 10.1149/1945-7111/ab68c6
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Li-O2 Batteries Enabled with Manganese Sulfide as Cathode Catalyst

Abstract: Transition metal sulfides (TMSs) are attracting great attention as cathode catalysts of Li-O 2 batteries. In this article, both γ-MnS and α-MnS are successfully synthesized and their performance is comparatively investigated when employed as cathode catalyst of Li-O 2 batteries. It reveals that both MnS materials are capable of catalyzing oxygen reduction reaction as well as oxygen evolution reaction, but α-MnS demonstrates higher activity and better reversibility. The batteries fabricated with α-MnS deliver h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…At present, the practicable bifunctional catalysts for Li–O 2 batteries mainly include carbon materials, precious metals and their alloys, and transition metal oxides (TMOs). In recent years, transition metal sulfides (TMSs) have also been in the spotlight due to their low price and excellent electronic and electrochemical properties, and some promising results have been achieved in this regard. As a member of TMSs, SnS 2 is cheap and easy to prepare and can be successfully synthesized into nanostructures with controllable morphology by a variety of synthetic methods. , Due to the graphene-like layered structure, SnS 2 has many applications in electrochemical devices including Li-ion batteries, photoelectronics, sensors, fuel cells, and so on. Our research group explored the catalytic properties of SnS 2 with different morphologies and found that a Li–O 2 battery based on plate-like SnS 2 exhibits superior performance compared to a battery with flower-like SnS 2 material judging from the ORR/OER kinetics, specific discharge capacity, rate capability, and life span. However, the cycleability of a plate-like SnS 2 -based battery is still unsatisfactory and needs promotion.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the practicable bifunctional catalysts for Li–O 2 batteries mainly include carbon materials, precious metals and their alloys, and transition metal oxides (TMOs). In recent years, transition metal sulfides (TMSs) have also been in the spotlight due to their low price and excellent electronic and electrochemical properties, and some promising results have been achieved in this regard. As a member of TMSs, SnS 2 is cheap and easy to prepare and can be successfully synthesized into nanostructures with controllable morphology by a variety of synthetic methods. , Due to the graphene-like layered structure, SnS 2 has many applications in electrochemical devices including Li-ion batteries, photoelectronics, sensors, fuel cells, and so on. Our research group explored the catalytic properties of SnS 2 with different morphologies and found that a Li–O 2 battery based on plate-like SnS 2 exhibits superior performance compared to a battery with flower-like SnS 2 material judging from the ORR/OER kinetics, specific discharge capacity, rate capability, and life span. However, the cycleability of a plate-like SnS 2 -based battery is still unsatisfactory and needs promotion.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest the fastest catalytic kinetics and the best reversibility of the ORR and OER reactions on YS-NCS-18 as catalysts for Li−O 2 batteries. Moreover, as listed in Table 1, the ORR peak voltage of YS-NCS-18 (2.345 V) is clearly higher than the reported values for Super P (2.132 V), 40 UC-NiCo 2 S 4 (2.274 V), 29 CoS 2 /RGO (2.300 V), 41 and NiMn 2 O 4 -FT (2.319 V), 42 and the OER peak voltage of YS-NCS-18 (3.224 V) is evidently lower than that of Super P (3.502 V), 40 UC-NiCo 2 S 4 (3.379 V), 29 CoS 2 /RGO (3.750 V), 41 NiMn 2 O 4 -FT (3.270 V), 42 MnS (3.233 V), 43 SnO 2 @C (3.465 V), 40 and NiCo 2 O 4 (4.250 V). 44 Therefore, it could be figured out that YS-NCS-18 possesses superior bifunctional electrocatalytic activity toward ORR/OER and the Li−O 2 battery with it in the cathode would express exciting performance.…”
Section: Resultsmentioning
confidence: 99%
“…After 60th charging, the charge transfer resistance slightly increased, indicating the excellent cycling performance of MnCo 2 S 4 -CoS 1.097 cathodes. In addition, compared with the most of the reported typical sulfides [46][47][48][49][50][51][52][53] and noble metals based cathodes (Figure 3h), [54][55][56][57][58][59][60][61][62] it is worth mentioning that the MnCo 2 S 4 -CoS 1.097 cathode deliver superior cycling stability under similar testing conditions.…”
Section: Resultsmentioning
confidence: 99%